Associations of Chronotype and Job Stressors with Anxiety, Depression, and Stress among Shift Workers in Oil and Gas Company - Fitria Nurbaeti; Feranindhya Agiananda; Levina Chandra Khoe; Dewi Sumaryani Soemarko; Imron Khazim (The Indonesian Journal of Community and Occupational Medicine, 2025)
Background: Oil and gas companies often require employees to work abnormal working hours, namely long shift hours and changing work environment conditions. Understanding how chronotypes, which refer to an individual’s biological preferences for choosing sleep and wake times (starting activities) and job stressors impact anxiety, depression, and distress levels among shift workers in oil and gas companies can aid in developing more effective risk management, health, and wellness programs for the workforce.Objective: This study aims to determine the relationship between chronotype and work stress with anxiety, depression, and stress in oil and gas companies.Methods: A cross-sectional study was conducted in an oil and gas company in Indonesia. Data was collected in 2024 using online questionnaires and interviews. Chronotype was measured using the Morningness Eveningness Questionnaire (MEQ) in Indonesian Version, job stressors were identified using the Stress Diagnostic Survey (SDS), and distress levels were obtained from the Depression Anxiety Stress Scale 21 (DASS 21). Results: Based on the results of data analysis, it was found that the chronotype type for workers in oil and gas companies is morning type as much as 57.4% and midnight type as much as 42.6%. From the results of the analysis, no relationship was found between chronotype and work stressors with stress levels. Chronotype type and work stressors are not related to the level of anxiety, depression and stress in the worker population in this study. The level of anxiety, depression and stress in workers was 20.5% and the prevalence of work stressors in workers experiencing moderate stress levels in the form of role inequality 54.9%, role conflict 52.5%, qualitative overload 52.5%, career development 50%, and responsibility for others 54.1%. While the most quantitative overload stressors were at the mild stress level 54.9%.Conclusion: The majority of respondents were morning type, and their job stressors were at moderate levels. The chronotype and job stressors did not have relationships with the level of distress. Other factors related to the incidence of anxiety, depression and stress levels in this study were age, length of service and type of work.